The Acetone Extract of Sclerocarya birrea (Anacardiaceae) Possesses Antiproliferative and Apoptotic Potential against Human Breast Cancer Cell Lines (MCF-7) - Nicoline Fri Tanih; Roland Ndip Ndip (The Scientific World Journal)
Interesting antimicrobial data from the stem bark of Sclerocarya birrea, which support its use in traditional medicine for the treatment of many diseases, have been delineated. The current study was aimed to further study some pharmacological and toxicological properties of the plant to scientifically justify its use. Anticancer activity of water and acetone extracts of S. birrea was evaluated on three different cell lines, HT-29, HeLa, and MCF-7 using the cell titre blue viability assay in 96-well plates. Apoptosis was evaluated using the acridine orange and propidium iodide staining method, while morphological structure of treated cells was examined using SEM. The acetone extract exhibited remarkable antiproliferative activities on MCF-7 cell lines at dose- and time-dependent manners (24 h and 48 h of incubation). The extract also exerted apoptotic programmed cell death in MCF-7 cells with significant effect on the DNA. Morphological examination also displayed apoptotic characteristics in the treated cells, including clumping, condensation, and culminating to budding of the cells to produce membrane-bound fragmentation, as well as formation of apoptotic bodies. The acetone extract of S. birrea possesses antiproliferative and apoptotic potential against MCF-7-treated cells and could be further exploited as a potential lead in anticancer therapy.